2014
DOI: 10.1097/iae.0b013e3182a2e6ee
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Outcomes of Pneumatic Retinopexy for Rhegmatogenous Retinal Detachments

Abstract: Several factors are associated with pneumatic retinopexy outcomes for rhegmatogenous retinal detachments. These factors should be taken into consideration when identifying patients who would benefit from pneumatic retinopexy and those who are at risk of requiring additional interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
5
24
2
1
Order By: Relevance
“…Additionally, the seminal randomized, controlled trial by Tornambe et al reported a 73% SOS rate with PR. 3 Two studies published in 2013 have reported SOS rates of 66.3% 19 and 60.7%, 20 respectively, which are consistent with the SOS from the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the seminal randomized, controlled trial by Tornambe et al reported a 73% SOS rate with PR. 3 Two studies published in 2013 have reported SOS rates of 66.3% 19 and 60.7%, 20 respectively, which are consistent with the SOS from the current study.…”
Section: Discussionsupporting
confidence: 91%
“… 16 This is in sharp contrast to the findings of this study and the lower rates reported by three recent studies that demonstrated a range of 60.7%–69.6%. 13 , 14 , 17 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Two recent large retrospective studies that investigated the risk factors for failure of PR reported an initial anatomical success rate of 61%–63.3% with a final rate of 96.1%–99.2%. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…All types of PR use the injection of an expanding gas bubble, without PPV, combined with laser photocoagulation or cryopexy to seal the retinal tear. Traditionally, PR is used for cases of RRD with specific preoperative characteristics: uncomplicated RRD with retinal breaks in the superior region (i.e., around the 8 o'clock position) or multiple superior breaks confined to a single clockwise sector, with a clear vitreous (Tornambe et al 1991;Gilca et al 2014). Recently, PR for primary repair of RRD has been reported to result in successful anatomic outcomes in about 75% of cases, including cases with various preoperative characteristics (Jung et al 2019 Older RRD patients with retinal tears in various regions, including GRT and PVR.…”
Section: Pneumatic Retinopexymentioning
confidence: 99%
“…That study found that PR resulted in superior VA, less vertical metamorphopsia, and reduced morbidity when compared with PPV. However, many reports have shown that the primary reattachment rate after PR is not very high (about 60-80%) (Han et al 1998;Gilca et al 2014;Goldman et al 2014;Hillier et al 2019;Jung et al 2019), in contrast with high reattachment rates after PPV (more than 90%) (Han et al 1998;Kunikata and Nishida 2010). Thus, PR is recommended in RRD patients with retinal tears in the superior region who desire to have the best possible visual function, even if additional procedures are needed, while PPV is recommended in patients with retinal tears in various regions who desire to avoid reoperations, regardless of the possible impact on visual functional recovery (Table 1).…”
Section: Pars Plana Vitrectomy Vs Pneumatic Retinopexymentioning
confidence: 99%